The Feasibility of Natural Orifice Transluminal Endoscopic Surgery in Gynecology Practice: Single-Surgeon Experience - Kaya, Cihan (Gynecol Minim Invasive Ther, 2020)
OBJECTIVES: Natural orifice transluminal endoscopic surgery (NOTES) has been performed in gynecology practice for the surgical treatment of ovarian cysts, uterine fibroids, ectopic pregnancies, adnexal masses, and pelvic organ prolapse. The aim of this study is to evaluate the intraoperative and postoperative outcomes of patients who underwent NOTES for gynecological diseases. MATERIALS AND METHODS: This study was a retrospective clinical study. The data of 50 patients who had been treated via NOTES procedure for benign gynecological indications such as ectopic pregnancy, adnexal mass, uterine fibroid, and treatment-resistant heavy menstrual bleeding during the time period between January 2016 and 2019 were included. All procedures were performed by a single surgeon (C.K.) using a self-constructed glove port, and a sealing device in addition to conventional laparoscopic (CL) equipment. Descriptive analysis of the patients' data was performed. RESULTS: The initial two of the adnexectomy procedures were performed via hybrid NOTES technic and four of them were performed via total vaginal NOTES technic. The remaining procedures, namely hysterectomies, adnexectomies, salpingectomies, and myomectomy were performed via vaginally assisted NOTES (VaNOTES) technic. The mean operation time for the hysterectomy ± bilateral salpingo-oophorectomy (BSO) and salpingo-oophorectomy patients was 85.25 min and 53.15 min, respectively. For those patients who underwent VaNOTES procedure, the median postoperative visual analog scale pain score at the 6(th)h was six and at the 24(th)h was two. The mean length of the hospital stay was 2.07 days in the hysterectomy ± BSO patients and 1.63 days in the salpingo-oophorectomy patients. CONCLUSION: The NOTES procedure is a feasible technic in regards to the duration of surgery, postoperative pain scores, and cosmetic outcomes.